Pengaruh Kepemilikan Saham Asing, Leverage, dan Capital Intensity terhadap Tax Avoidance dengan Manajemen Laba sebagai Variabel Intervening (Studi Empiris pada Perusahaan Sektor Manufaktur di BEI Tahun 2020–2024) - Tuanda Jhonson Purba, Tri; Nausta Pardede, Tiolina Evi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of foreign share ownership, leverage, and capital intensity on tax avoidance with earnings management as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study employs a quantitative approach using secondary data obtained from the companies’ annual financial reports. The sample was determined through purposive sampling techniques based on specific criteria, resulting in 97 companies that met the research requirements. The analytical method applied is panel data regression using the Fixed Effect Model (FEM) approach to examine the relationships among variables both partially and simultaneously. The findings indicate that foreign share ownership, leverage, and capital intensity each have a negative and significant effect on tax avoidance. These results suggest that higher levels of foreign ownership, leverage, and capital intensity tend to reduce the likelihood of companies engaging in tax avoidance practices. Furthermore, the Sobel test results reveal that earnings management is capable of mediating the effect of foreign share ownership on tax avoidance. However, earnings management is not proven to mediate the relationship between leverage and capital intensity on tax avoidance in the manufacturing companies examined in this study.